2019
DOI: 10.1289/ehp3971
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Urban Exposome on Birth Weight

Abstract: Background:The exposome is defined as the totality of environmental exposures from conception onwards. It calls for providing a holistic view of environmental exposures and their effects on human health by evaluating multiple environmental exposures simultaneously during critical periods of life.Objective:We evaluated the association of the urban exposome with birth weight.Methods:We estimated exposure to the urban exposome, including the built environment, air pollution, road traffic noise, meteorology, natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 56 publications
4
67
3
Order By: Relevance
“…Interestingly, n our urban and suburban pregnancy cohort, access to signi cantly moderated the association between residential proximity to tra c and maternal biological stress in the 2 nd pregnancy trimester. Bene cial relationships between residential access to greenspace and hair cortisol concentrations have been described in previous studies [56,57]; whereas other studies have reported a bene cial impact of surrounding greenness on fetal growth and birth weight [58][59][60][61]. Neighborhood greenspace may improve health by relieving psychophysiological stress, supporting physical activity, increasing social contacts and by reducing exposure to air pollution, noise and excessive heat [62][63][64][65].…”
Section: Discussionmentioning
confidence: 82%
“…Interestingly, n our urban and suburban pregnancy cohort, access to signi cantly moderated the association between residential proximity to tra c and maternal biological stress in the 2 nd pregnancy trimester. Bene cial relationships between residential access to greenspace and hair cortisol concentrations have been described in previous studies [56,57]; whereas other studies have reported a bene cial impact of surrounding greenness on fetal growth and birth weight [58][59][60][61]. Neighborhood greenspace may improve health by relieving psychophysiological stress, supporting physical activity, increasing social contacts and by reducing exposure to air pollution, noise and excessive heat [62][63][64][65].…”
Section: Discussionmentioning
confidence: 82%
“…The selection of exposures to consider in the study depends on the research question and issues of feasibility and data accessibility. Previous studies have included a wide range of external environmental exposures from various families, or have been specifically focused on certain components of the exposome, such as the urban or the chemical exposome, assessed at various developmental periods [13][14][15][16][17][18][19]. Socioand public health exposome conceptual frameworks have also been proposed and can guide the selection of exposures [20,21].…”
Section: Selecting and Pre-processing Exposuresmentioning
confidence: 99%
“…The DSA algorithm was used, for instance, in recent studies within the HELIX project looking at the associations between the early-life exposome and childhood lung function and between the urban pregnancy exposome and birth weight [13,16]. The DSA algorithm is an iterative model search algorithm that relies on deletion (removing one variable from the model), substitution (replacing one variable from the model by one that was not yet included in the model) or addition (adding one new variable to the model) moves to find the optimal set of variables that minimizes the root mean square error.…”
Section: Variable Selection Techniquesmentioning
confidence: 99%
“…69 Several aspects of the urban exposome, such as green space, bus lines close to residential addresses, and lower building density are linked to improved birth outcomes. 70 Urban green space is perhaps the best example of an environmental factor that may act as a public health good.…”
Section: Environmental Exposures and Birthweight Outcomesmentioning
confidence: 99%
“…160 In a large review of the urban exposome and birth outcomes, green space emerged as the protective factor with the most consistent association with improved outcomes. 70 A systematic review in 2017 found reasonable support for a positive association between green space and birthweight, mixed results for gestational length, and limited studies on outcomes such as head circumference, Apgar score, and mortality. 161…”
Section: Birth Outcomesmentioning
confidence: 99%